ERRATUM: Plant growth-promoting bacteria isolated from sugarcane improve the survival of micropropagated plants during acclimatisation - Michavila, Gabriela; Alibrandi, Pasquale; Cinà, Paolo; Welin, Bjorn; Castagnaro, Atilio Pedro; Chalfoun, Nadia Regina; Noguera, Aldo Sergio; Puglia, Anna Maria; Ciaccio, Mirella; Racedo, Josefina (Italian Journal of Agronomy, 2022)
Due to a mistake, the affiliation of Prof. Anna Maria Puglia was incorrectly reported in this article, published in Italian Journal of Agronomy in 2022 (DOI: 10.4081/ija.2022.2006). The correct affiliation appears above. Italian Journal of Agronomy DOI: 10.4081/ija.2022.2150